2019
DOI: 10.1101/848325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BET inhibition disrupts transcription but retains enhancer-promoter contact

Abstract: In higher eukaryotes, enhancers are DNA sequences that enable complex temporal and tissue-specific regulation of genes. Although it is not entirely clear how enhancer-promoter interactions can increase gene expression, this proximity has been observed in multiple systems at multiple loci and is thought to be essential for the maintenance of gene expression. The formation of phase condensates is thought to be an essential component of enhancer function. Here, we show that pharmacological targeting of cells with… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 90 publications
2
29
0
Order By: Relevance
“…For example, it has been shown that inhibition of BRD4 [ 87 ] binding or general perturbation of protein condensation by 1,6-hexanediol [ 91 ] treatment result in dissolution of large Med1, BRD4, and PolII condensates in mouse PSCs, preferential loss of SE activity and downregulation of many associated genes. Interestingly, some recent studies demonstrated that although these treatments have drastic effects on enhancer activity and gene expression, they do not affect 3D chromatin organization and enhancer–promoter contacts [ 95 ], arguing against the role of BRD4 and/or protein condensation in long-range interactions. Similarly, inhibition of transcription per se seems to have very little impact on promoter–enhancer contacts [ 95 , 96 ].…”
Section: Mechanisms Of Loop and Hub Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that inhibition of BRD4 [ 87 ] binding or general perturbation of protein condensation by 1,6-hexanediol [ 91 ] treatment result in dissolution of large Med1, BRD4, and PolII condensates in mouse PSCs, preferential loss of SE activity and downregulation of many associated genes. Interestingly, some recent studies demonstrated that although these treatments have drastic effects on enhancer activity and gene expression, they do not affect 3D chromatin organization and enhancer–promoter contacts [ 95 ], arguing against the role of BRD4 and/or protein condensation in long-range interactions. Similarly, inhibition of transcription per se seems to have very little impact on promoter–enhancer contacts [ 95 , 96 ].…”
Section: Mechanisms Of Loop and Hub Formationmentioning
confidence: 99%
“…Interestingly, some recent studies demonstrated that although these treatments have drastic effects on enhancer activity and gene expression, they do not affect 3D chromatin organization and enhancer–promoter contacts [ 95 ], arguing against the role of BRD4 and/or protein condensation in long-range interactions. Similarly, inhibition of transcription per se seems to have very little impact on promoter–enhancer contacts [ 95 , 96 ]. These data together argue that the transcriptional activity of a gene and the physical interaction with enhancer(s) are separable events.…”
Section: Mechanisms Of Loop and Hub Formationmentioning
confidence: 99%
“…Although strong evidence has revealed that proximity of enhancers and promoters may be a driver of transcription, in some cases, enhancer–promoter interaction alone might not be sufficient to drive transcription. In a recent study performing Capture-C approach at over 60 loci to test the impact of BET inhibitors on enhancer–promoter interactions and transcriptional change in an acute lymphoblastic leukemia cell line, the authors found that BET inhibition has a strong effect on transcription but enhancer–promoter interactions remained undisrupted ( 48 ). In addition, upon glucocorticoid treatment, glucocorticoid receptor (GR) did not reorganize chromatin looping but bound on the sites with pre-established enhancer–promoter interactions and modulated gene transcription ( 49 ).…”
Section: Enhancer–promoter Interaction: a Driver Or Passenger For Genmentioning
confidence: 99%
“…For the DOT1L model we used nascent RNA-seq of SEM cells treated for 7 days with the DOT1L inhibitor (DOT1Li) EPZ-5676 (38,83), along with H3K79me3 ChIP-seq (38) as a proxy for DOT1L binding (Supplementary Figure S1B). The BRD4 network made use of published nascent RNA-seq of SEM cells treated with IBET-151 for 1.5 hours to inhibit BRD4 binding to chromatin (67) and BRD4 ChIP-seq (60) (Supplementary Figure S1C). We found that, while many of the MLL-AF4 GRN nodes are affected by IBET and DOT1Li treatment, not all of the most central nodes are impacted (Supplementary Figure S1D).…”
Section: The Mll-af4 Fusion Protein Controls a Wider Transcription Famentioning
confidence: 99%